BIOASSAYS FOR MEASURING THE ACARICIDES SUSCEPTIBILITY OF CATTLE TICK BOOPHILUS MICROPLUS (CANESTRINI, 1887) IN SÃO PAULO STATE, BRAZIL - Mendes, M.c.; Veríssimo, C.j.; Kaneto, C.n. [UNESP]; Pereira, J.r. (Instituto Biológico, 2024)
The susceptibility of Boophilus microplus tick to acaricides was evaluated on farms located in different regions of São Paulo State. The method used for the evaluation was the immersion of engorged tick females in commercial formulation of the chemical groups organophosphate, pyrethroids, amitraz and the association between organophosphate and pyrethroid. The efficacy of pyrethroid acaricides was lower than 50% in all regions studied. The association between the organophosphate and pyrethroid had the mean efficacy higher than 90% in the North Region, and the amitraz had efficacy higher than 90% in the Northwest and Southern Regions. This work shows the low efficacy of pirethroids acaricides on Boophilus microplus in São Paulo State nowadays.

Foram avaliadas amostras de carrapato Boophilus microplus provenientes de fazendas localizadas em diferentes regiões do Estado de São Paulo. O método usado foi de imersão de teleóginas em formulações comerciais dos grupos químicos organofosforado, piretróide, amitraz e associação organofosforado e piretróide. A eficácia de produtos à base de piretróides foi inferior a 50% em todas as regiões avaliadas; a eficácia média da associação entre o produto organofosforado e o piretróide foi superior a 90% na região norte do Estado. O amitraz teve, em média, eficácia superior a 90% nas regiões sudeste e noroeste. Constatou-se a baixa eficiência que vêm tendo atualmente os produtos piretróides sobre cepas de Boophilus microplus provenientes de várias regiões do Estado de São Paulo.
BIOENSAIO PARA AVALIAR A SENSIBILIDADE DO CARRAPATO Boophilus microplus (CANESTRINI,1887) A CARRAPATICIDAS NO ESTADO DE SÃO PAULO, BRASIL
Keywords: Boophilus microplus; pyrethroids; organophosphate; amitraz; resistance.; Boophilus microplus; piretróides; organofosforados; amitraz; resistência.